Promoting a local and just green deal. School open spaces as a strategic opportunity for the city in the ecological transition - Gisotti, Maria Rita; Masiani, Benedetta (TeMA - Journal of Land Use, Mobility and Environment, 2024)
Recent global policies like the United Nations 2030 Agenda, Paris Agreements, and European Green Deal emphasise the urgency of sustainable lifestyles, production, and mobility. However, there are associated risks, including the exacerbation of socioeconomic inequalities and an overemphasis on large infrastructure projects. The ongoing debate recognizes the need for a place-based approach, with cities at the core of the European transition and active citizen engagement. European institutions address these challenges through initiatives like the "Green Deal Going Local" by the Committee of the Regions, the European Commission's "Local Green Deals," and the "New European Bauhaus" for cultural and social transition. This paper argues that schools, especially open spaces, can play a key role in implementing a local, sustainable and equitable green deal. They can facilitate participatory processes, promote a sense of citizenship and function as laboratories for green urban regeneration. To verify this hypothesis, the paper examines European policies and best practices in the regeneration of school open spaces in Europe from 2019 to the present. These practices are assessed on the basis of key strategic issues and governance principles for a local and fair transition. Finally, research results are discussed together with potential pathways for the implementation of actions related to the local Green Deal.